Books Reviews - Komarovski, Yaroslav; Stasik, Danuta (Acta Orientalia Vilnensia, 2010)
Yaroslav Komarovski. Visions of Unity: the Golden Paṇḍita Shakya Chokden’s new interpretation of Yogācāra and Madhyamaka, Albany: State University of New York Press, 2011, pp. xii+451. ISBN 978-1-4384-3909-9 (Hardcover), 90.00 Danuta Stasik. The Infinite Story. The Past and Present of the Rāmāyaṇas in Hindi, New Delhi: Manohar, 2009, pp. 319. ISBN 978-81-7304-815-9 (Hardbound)